PENERAPAN MODEL PEMBELAJARAN RADEC TERHADAP PENINGKATAN KEMAMPUAN LITERASI NUMERASI SISWA - Ardianti, Sri; Lestari, Hana; Trimulyo, Joko (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
Numeracy literacy is a student's ability to apply the concept of numbers, numbers and symbols and interpret quantitative information in everyday life. Numeracy literacy skills can be improved through the RADEC learning model. This research aims to determine the application of the RADEC learning model to improving students' numeracy literacy skills. The method used was pre-experiment with a one-group pretest-posttest design. The research was conducted on class V students at MI Darul Muttaqin, Cibungbulang District, Bogor. The sample in this study used nonprobability sampling with a saturated sample of 23 students from class V. The instruments used were tests on students' numeracy literacy skills and observation sheets. The numeracy literacy ability test was carried out in two stages, namely the pretest and posttest stages. From the research, it was found that the average score for students' numeracy literacy skills on the pretest was 11.7, while the average score on the posttest was 21.65. Data processing was analyzed using SPSS 21 for Windows with the Paired Sample t-test at α (0.001) and obtained a sig value of 0.000 < α (0.001). The research results showed that there was a significant difference between the pretest and posttest. It can be interpreted that there is an increase in students' numeracy literacy skills before and after treatment using the RADEC learning model.